2020
DOI: 10.3390/su12166604
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Spider Plants (Gynandropsis gynandra, L. Briq) amongst Farming Households and Consumers of Northern Namibia

Abstract: Spider plants (Gynandropsis gynandra, L. Briq.) are a semi-wild vegetable reported to have high nutritional, medicinal, insecticidal, and cultural values, yet continue to be neglected in research. The study was undertaken to investigate indigenous knowledge and utilization of the species in five regions of northern Namibia. Three tools were used; (i) focus group discussion, (ii) semi-structured interviews involving a random selection of 100 farming households and 24 consumers, and (iii) key informant interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Furthermore, the antioxidants are reported to reduce DNA damage (Sevgi et al, 2015) and are believed to have antiaging and vitality strengthening properties (Giri et al, 2017). The results from this study suggest that the spider plant is a source of antioxidants, and this supports its use in traditional medicine (Chataika et al, 2020). Sowinmi and Afolayan (2015) also observed that G. gynandra possessed high secondary metabolites, which accounted for its strong antioxidant ability, thus justifying its use as naturally occurring antioxidants in folkloric medicine.…”
Section: Antioxidant Activity Of Different Accessions Of Spider Plantmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, the antioxidants are reported to reduce DNA damage (Sevgi et al, 2015) and are believed to have antiaging and vitality strengthening properties (Giri et al, 2017). The results from this study suggest that the spider plant is a source of antioxidants, and this supports its use in traditional medicine (Chataika et al, 2020). Sowinmi and Afolayan (2015) also observed that G. gynandra possessed high secondary metabolites, which accounted for its strong antioxidant ability, thus justifying its use as naturally occurring antioxidants in folkloric medicine.…”
Section: Antioxidant Activity Of Different Accessions Of Spider Plantmentioning
confidence: 53%
“…Nevertheless, this study detected a relatively weak correlation between total tannins and antioxidant activity, thus suggesting the need for further studies to determine the levels and antioxidant activities of the different types of tannins in spider plant. Additionally, the presence of tannins was reported to be responsible for the astringent taste (Kutsututsa et al, 2014) and influenced the palatability and utilization of the vegetable (Chataika et al, 2020). Identifying specific types of tannins and their antioxidant potential in different accessions of spider plant would therefore aid in targeted nutraceutical breeding for addressing specific human health and nutrition disorders and genetic improvements in the species.…”
Section: Discussion Phytochemical Content In Different Accessions Of Spider Plantmentioning
confidence: 99%
“…Cleome gynandra belongs to the Cleomaceae family and is indigenous to sub-Saharan Africa (SSA) and South-east Asia (Bala et al, 2010;Munene et al, 2018;Shilla et al, 2019). In SSA, it is particularly found in many countries which includes Botswana, Kenya, Malawi, Namibia, South Africa, Tanzania, Uganda, Zambia and Zimbabwe (Vorster et al, 2002;Mauyo et al, 2008;Onyango et al, 2013;Jinazali et al, 2017;Omondi et al, 2017;Chataika et al, 2020). Additionally, it has been found growing naturally in seven of the nine South African provinces, which are Limpopo, Northwest, Gauteng, Mpumalanga, KwaZulu-Natal, Free State and Northern Cape (Mishra et al, 2011;Mabhaudhi et al, 2017).…”
Section: Cleome Gynandra Highly Neglected But Found Across Tropical A...mentioning
confidence: 99%
“…Most studies have shown association amongst socio-demographic and socio-economic factors in the utilisation of the spider plant. For example, authors such as Kiebre et al (2015), Voster et al (2007), Sogbohossou et al (2018a), andChataika et al (2020a) reported differences in the utilisation of spider plant as a result of cultural belief and influence, tradition and geographical separation, ethnicity, norms, and availability of the species. Gynandropsis gynandra is regarded as an efficient medicinal plant in several African and Asian countries.…”
Section: Ethnobotanical Investigations For Increased Nutraceutical Be...mentioning
confidence: 99%
“…Spider plant leaves are sometimes cooked with other species, such as Amaranthus spp., to improve the taste. Sometimes, cooked leaves are dried and flattened into cakes, locally known as 'omavanda' in Namibia, for off-season use or to sell at the open markets (Chataika et al, 2020a).…”
Section: Ethnobotanical Investigations For Increased Nutraceutical Be...mentioning
confidence: 99%